Assessing earthworm exposure to a multi-pharmaceutical mixture in soil: unveiling insights through LC–MS and MALDI-MS analyses, and impact of biochar on pharmaceutical bioavailability - Fučík, Jan; Jarošová, Rea; Baumeister, Andreas; Rexroth, Sascha; Navrkalová, Jitka; Sedlář, Marian; Gargošová, Helena Zlámalová; Mravcová, Ludmila (Environmental science and pollution research international, 2024)
In the European circular economy, agricultural practices introduce pharmaceutical (PhAC) residues into the terrestrial environment, posing a potential risk to earthworms. This study aimed to assess earthworm bioaccumulation factors (BAFs), the ecotoxicological effects of PhACs, the impact of biochar on PhAC bioavailability to earthworms, and their persistence in soil and investigate earthworm uptake mechanisms along with the spatial distribution of PhACs. Therefore, earthworms were exposed to contaminated soil for 21 days. The results revealed that BAFs ranged from 0.0216 to 0.329, with no significant ecotoxicological effects on earthworm weight or mortality ( p > 0.05). Biochar significantly influenced the uptake of 14 PhACs on the first day ( p < 0.05), with diminishing effects over time, and affected significantly the soil-degradation kinetics of 16 PhACs. Moreover, MALDI-MS analysis revealed that PhAC uptake occurs through both the dermal and oral pathways, as pharmaceuticals were distributed throughout the entire earthworm tissue without specific localization. In conclusion, this study suggests ineffective PhAC accumulation in earthworms, highlights the influence of biochar on PhAC degradation rates in soil, and suggests that uptake can occur through both earthworm skin and oral ingestion. Graphical Abstract